(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2016)
This paper argues that propositional modal logics based on Kripke-structures cannot be accepted by epistemologists as a minimal framework to describe propositional knowledge. In fact, many authors have raised doubts over the validity of the so-called principle of epistemic closure, which is always valid in normal modal logics. This paper examines how this principle might be criticized and dis- cusses one possible way to obtain a modal logic where it does not hold, namely through the introduction of impossible worlds..